REVITALISASI WISATA RELIGI LAMONGAN MELALUI LITERASI DIGITAL DAN PENYUSUNAN NARASI BUDAYA ISLAM NUSANTARA - Mujanah, Siti; Sumiati, Sumiati (Semeru: Jurnal Pengabdian Kepada Masyarakat, 2025)
The revitalization of religious tourism in the local culture-based area requires an adaptive approach to technological developments and the preferences of the digital generation. This article aims to increase the capacity of the community in managing religious tourism in Lamongan through digital literacy and the preparation of the archipelago's Islamic cultural narrative. Using a qualitative approach with participatory observation methods, in-depth interviews, and Focus Group Discussions (FGD), this activity involved local tourism actors, MSME actors, and cultural leaders in training in digital content creation and strengthening local cultural identity. The results of the activity show a significant increase in people's digital skills and the creation of cultural narratives that can be published online. These findings contribute to community empowerment and strengthening the theory of cultural communication in the context of tourism promotion. In conclusion, digital literacy and local cultural narratives are strategic instruments in strengthening the attraction of religious tourism. Further research is recommended to evaluate the long-term effectiveness of this program in increasing tourism visits and cultural preservation.